Students' Listening Skills in Indonesian Language and Literature Learning Through Listening Learning Program Design - Reni Oktaviani (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
This study aims to analyze in depth the listening skills of students and describe the design of a contextual, systematic listening learning program that is oriented towards developing students' communicative and appreciative competencies. This study uses a qualitative descriptive approach and literature review of various listening learning models and student characteristics. The results of this study indicate that an effective listening learning program design must include appropriate and focused learning objective planning, selection of materials according to needs, active learning strategies, and continuous evaluation. With an appropriate and high-quality learning design, students' listening skills can develop optimally and contribute significantly to the success of Indonesian language and literature learning.